Refractory Craniopharyngioma: Successful Treatment with LINAC Based Stereotactic Radiosurgery (SRS): First Case in Nepal - Thakur, Subhash; Chawla, Saloni (Asian Pacific Journal of Cancer Care, 2021)
Purpose: To present first case of refractory craniopharyngioma treated successfully with SRS in Nepal. Bckground: Craniopharyngioma is a benign tumour, which progresses slowly and compresses the pituitary gland and nearby structures. First line of treatment is surgery followed by adjuvant radiotherapy as complete resection is usually not feasible. Here, we are reporting a case of recurrent craniopharyngioma treated with LINAC based SRS. Case Presentation: A 43 years old man diagnosed case of craniopharyngioma in May 2019. He underwent left pterional craniotomy and subtotal resection of tumour and kept on observation. He developed symptomatic as well as radiological recurrence in July 2020. Second debulking was not possible, so we did SRS on 23rd August 2020; 14Gy Dose was delivered to gross tumour volume. Six months after SRS, Patient is doing well. Conclusions: LINAC based SRS is a frameless, non-invasive and safe procedure with excellent clinical outcomes for recurrent or residual craniopharyngioma.